2023
DOI: 10.1002/jsfa.12867
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of consumer acceptability of cassava gari‐eba food products across cultural and environmental settings using the triadic comparison of technologies approach (tricot)

Abstract: BACKGROUNDNigeria and Cameroon are multi‐ethnic countries with diverse preferences for food characteristics. The present study aimed to inform cassava breeders on consumer‐prioritized eba quality traits. Consumer testing was carried out using the triadic comparison of technologies (tricot). Diverse consumers in villages, towns and cities evaluated the overall acceptability of eba made from different cassava genotypes. Data from both countries were combined and linked to laboratory analyses of eba and the gari … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The G+ tool was used to document trait trade-offs (Forsythe et al, 2021;Polar et al, 2022) to corroborate priority ranks assigned to the traits. Going beyond sensory traits (e.g., taste), our studies also identified the influence of sociodemographic characteristics, location and food habits on the preferred quality traits of gari and eba in Nigeria Olaosebikan et al, 2023). There is now a well-established and cordial relationship among the economists, data curators, application developers, data analysts, statisticians, breeders, social scientists and food scientists as they work together to analyze traits and present them in an easy-to-understand format that can be incorporated into the breeding programs.…”
Section: Analysis Multidisciplinary Approach For Inclusive Cassava Br...mentioning
confidence: 73%
See 1 more Smart Citation
“…The G+ tool was used to document trait trade-offs (Forsythe et al, 2021;Polar et al, 2022) to corroborate priority ranks assigned to the traits. Going beyond sensory traits (e.g., taste), our studies also identified the influence of sociodemographic characteristics, location and food habits on the preferred quality traits of gari and eba in Nigeria Olaosebikan et al, 2023). There is now a well-established and cordial relationship among the economists, data curators, application developers, data analysts, statisticians, breeders, social scientists and food scientists as they work together to analyze traits and present them in an easy-to-understand format that can be incorporated into the breeding programs.…”
Section: Analysis Multidisciplinary Approach For Inclusive Cassava Br...mentioning
confidence: 73%
“…As a result of the successful gender studies, cassava breeding initiatives have recently prioritized two more food product profiles, focused on food security, and on improved nutritional quality and industrial needs. These include (1) processed foods, which extend the short shelf life of the cassava root, and (2) fresh cassava for eating after boiling at times of the year when yam is expensive or unavailable (Olaosebikan et al, 2023 ).…”
Section: Methods and Approachesmentioning
confidence: 99%
“…mainly done by women, then the breeders' decision may have exacerbated gender inequality and increased the probability that women will avoid or discourage planting the variety (e.g. Dufour et al, 2023; see also, GBI diagram of breeders' critical decision points).…”
Section: Priorities For Gender Researchmentioning
confidence: 99%
“…The design of gender-intentional product profiles requires a thorough characterization and understanding of the GI seed-based market segments, concerning gender demographics and gender relations in the crop's production or its use. This involves screening end-user populations for diversity that drives their varietal choice and adoption, analogous to screening for genetic diversity in plant populations ( van Etten et al 2023).…”
Section: Priority 1: Gender Mapping Of Market Segmentsmentioning
confidence: 99%
See 1 more Smart Citation